2019
DOI: 10.1021/acs.joc.9b02174
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Os-Catalyzed Oxidative Cyclization of 1,5-Dienes

Abstract: The oxidative cyclization of 1,5-dienes by metal oxo species is a powerful method for stereocontrolled synthesis of tetrahydrofuran diols (THF-diols), structural motifs present in many bioactive natural products. Oxidative cyclization of (2E,6E)-octa-2,6-diene catalyzed by OsO4/NMO as has been studied using density functional theory (DFT) calculations (M06-2X/augcc-pVDZ/Hay-Wadt VDZ (n+1) ECP), highlighting the remarkable effect of acid on the fate of the first intermediate, an Os(VI) dioxoglycolate. Strong ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…In 2010, a DFT study of the oxidative cyclization of 1,5-dienes by OsO 4 was reported by Poethig and Strassner, where the reaction pathway was built on two key steps: alkene osmylation and cyclization via Os­(VIII) glycolate intermediate to form the THF ring . However, Donohoe and co-workers showed that the cyclization is viable through a protonated Os­(VI) intermediate. , In 2019, our DFT study emphasized the remarkable impact of Bro̷nsted acid on the fate of cyclization through NMO-complexed Os­(VI) dioxoglycolate ( E , Figure b) . Our findings revealed a potential catalytic cycle wherein oxidation of the cyclized NMO-complexed Os­(IV) THF-diolate intermediate F to the corresponding Os­(VI) species G occurs, followed by slow hydrolysis and eventual regeneration of OsO 4 .…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…In 2010, a DFT study of the oxidative cyclization of 1,5-dienes by OsO 4 was reported by Poethig and Strassner, where the reaction pathway was built on two key steps: alkene osmylation and cyclization via Os­(VIII) glycolate intermediate to form the THF ring . However, Donohoe and co-workers showed that the cyclization is viable through a protonated Os­(VI) intermediate. , In 2019, our DFT study emphasized the remarkable impact of Bro̷nsted acid on the fate of cyclization through NMO-complexed Os­(VI) dioxoglycolate ( E , Figure b) . Our findings revealed a potential catalytic cycle wherein oxidation of the cyclized NMO-complexed Os­(IV) THF-diolate intermediate F to the corresponding Os­(VI) species G occurs, followed by slow hydrolysis and eventual regeneration of OsO 4 .…”
Section: Introductionmentioning
confidence: 72%
“…However, upon protonation and complexation, a low energy gap is obtained in agreement with the low barrier of cyclization being calculated for Int20 (9.9 kcal/mol via TS18 ) and Int24 (12.8 kcal/mol via TS14 ) (Figure ). The low barriers for oxo-protonated or alkoxy-protonated Os­(VI) intermediates Int20 and Int24 are clearly attributed to the decrease in LUMO orbitals, increasing the electrophilicity of the Os center …”
Section: Resultsmentioning
confidence: 99%
“…8). This type of reaction has been studied for OsO 4 53,54 or RuO 4 55 on simple aromatic systems or double bonds. DFT calculations confirmed the good affinity between the ditopic ligand of UiO-66-NH 2 and RuO 4 , through strong hydrogen bonding between the porous framework (from NH 2 groups connected to neighboring ligands) and the gaseous species in intermediate 1.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, proton transfer from chlorous acid represents the first-half pathway, from the pre-reaction complex until the TS, with a noticeable change of the bond length near TS. Due to significant differences between the progressions of the two bond formations O-H and C-O in the TS 8, it would be valuable to get more validations on PES towards the chronological formation of these bonds from the point of molecular dynamic (MD) simulations, especially the behaviour of the system within time (figure 8) (for the molecular dynamics on transition state structures see: [60][61][62][63][64][65][66]). Classical MD calculations were carried out on one trajectory, where the forward and backward propagation of TSs are initiated in the region of the PES near the TS (t = 0 fs) showing the typical reactive bonds toward intermediate 9 and reactants (acrylaldehyde and chlorous acid).…”
Section: Irc and MD Simulations Of The Frsmentioning
confidence: 99%
“…open sci. 7: 191568 structures see:[60][61][62][63][64][65][66]). Classical MD calculations were carried out on one trajectory, where the forward and backward propagation of TSs are initiated in the region of the PES near the TS (t = 0 fs) showing the typical reactive bonds toward intermediate 9 and reactants (acrylaldehyde and chlorous acid).…”
mentioning
confidence: 99%